2014
DOI: 10.1093/mnras/stu2272
|View full text |Cite
|
Sign up to set email alerts
|

Chemoarchaeological downsizing in a hierarchical universe: impact of a top-heavy IGIMF

Abstract: We make use of a semi-analytical model of galaxy formation to investigate the origin of the observed correlation between [α/Fe] abundance ratios and stellar mass in elliptical galaxies. We implement a new galaxy-wide stellar initial mass function (Top Heavy Integrated Galaxy Initial Mass Function, TH-IGIMF) in the semi-analytic model SAG and evaluate its impact on the chemical evolution of galaxies. The SFR-dependence of the slope of the TH-IGIMF is found to be key to reproducing the correct [α/Fe]-stellar mas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(101 citation statements)
references
References 133 publications
(194 reference statements)
5
91
0
5
Order By: Relevance
“…This feature remains a shared standard for semi-analytic models in general (see the latest versions of other models, e.g. Gargiulo et al 2015;Henriques et al 2015;Lacey et al 2016). If subhaloes were able to accrete hot gas from the ICM within a semi-analytic framework, this should systematically raise H i fractions and lower quiescent fractions.…”
Section: Caveats Discussion and Conclusionmentioning
confidence: 96%
“…This feature remains a shared standard for semi-analytic models in general (see the latest versions of other models, e.g. Gargiulo et al 2015;Henriques et al 2015;Lacey et al 2016). If subhaloes were able to accrete hot gas from the ICM within a semi-analytic framework, this should systematically raise H i fractions and lower quiescent fractions.…”
Section: Caveats Discussion and Conclusionmentioning
confidence: 96%
“…Simultaneously explaining the increasing α-to-Fe ratio with velocity dispersion (or stellar mass) and increasing stellar metallicity with stellar mass is therefore fundamentally difficult within the current framework of galaxy formation. One possible solution would be the introduction of a variable IMF which becomes more top-heavy for a higher SFR as suggested by Calura & Menci (2009) and Gargiulo et al (2015) and previously suggested on independent grounds by Baugh et al (2005) and Lacey et al (2016).…”
Section: S U M M a Ry A N D Discussionmentioning
confidence: 99%
“…They found that a combination of a power-law DTD and metal-rich winds, which drive light α elements directly out of galaxies, gives the best agreement with a wide range of observational data including the [α/Fe]-mass and mass-metallicity relations. On the other hand, Gargiulo et al (2015) employed a variable IMF whose slope becomes shallower (more top-heavy) for a higher SFR of a galaxy. They tuned their model to reproduce the observed [α/Fe]-galaxy mass relation, and they claimed that the SFR-dependent IMF is key to reproducing the [α/Fe]-galaxy mass relation and that a short star formation time-scale due to radio-mode AGN feedback alone cannot explain the slope of the relation.…”
Section: Introductionmentioning
confidence: 99%
“…While the treatment of mergers is the same as the one implemented in previous versions of SAG, many aspects of DI have been modified for the purposes of the present study. Both mechanisms trigger starbursts that involve a timescale that regulates the consumption of the cold gas involved in the process as implemented by Gargiulo et al (2015), instead of being instantaneous as in former versions of SAG. We refer the reader to their work for more details about the treatment of extended bursts.…”
Section: Bulge Formation Mechanismsmentioning
confidence: 99%
“…It follows the production of eleven chemical elements (H, 4 He, 12 C, 14 N, 16 O, 20 Ne, 24 Mg, 28 Si, 32 S, 40 Ca, 56 Fe) generated by stars in different mass ranges. As described in Gargiulo et al (2015), we adopt a new set of stellar yields given by Karakas (2010), (Hirschi et al 2005) and Kobayashi et al (2006) for low and intermediate-mass stars (mass interval 1 − 8M ⊙ ), for the mass loss of pre-supernova stars (He and CNO elements), and for the explosive nucleosynthesis (SNe CC), respectively, all of them corresponding to solar metallicities. These yields are selected to be in accordance with the large number of constraints for the Milky Way (Romano et al 2010).…”
Section: Chemical Enrichment Modelmentioning
confidence: 99%